G515(P) Specifying eligibility criteria in the referral process reduces delay in decision making and access to services in a children's hospice. (24th May 2017) - Hunter, M
Abstract : Aims: Children's hospices provide a range of services for children with life limiting (LLC) and life threatening conditions (LTC). Referral previously relied on obtaining supporting views from the child's paediatrician and there was often delay between referral and decision about eligibility being made. This abstract reports the effect of a revised referral process on the time to decision. Method: Referral processes and documentation were changed to explicitly link eligibility with the categories of LLC and LTC published by Together for Short Lives (TfSL). This was accompanied by education sessions for professionals. All referrals received during 3 month periods before and after the change were examined and data obtained about the time delay between referral and decision. Results: Before Change: 52 referrals received, 3 declined. 7 referrals for end of life care, all accepted on the day of referral Overall 14/52 (27%) of decisions were made on day referral received or first reviewed: Mean delay between receipt and decision: 22 days (30 days if further information requested) After Change: 61 referrals received, 4 declined 9 referrals for end of life care, all accepted on the day of referral Overall 42/61 (69%) of decisions were made on the day referral received or first reviewed: Mean delay between receipt and decision: 8 days (26 days if further information requested) Conclusion: The changes made to the referral process have significantly reduced delays in decision making and access to services. There remains a significant delay in decision making for those in TfSL catgory 4 (long-term conditions with additional complications or vulnerabilities) and more work is needed to better identify those eligible for hospice services.